Athletic development: the art & science of functional sports conditioning - Gambetta, V. (Human Kinetics, 2007)
In Athletic Development, world-renowned strength and conditioning coach Vern Gambetta condenses the wisdom he's gained through more than 40 years of experience working with athletes across many sports, age groups, and levels of competition. The result is an information-packed explanation of the most effective methods and prescriptions for each facet of an athlete's physical preparation, including